Compound nucleating agent as well as preparation method and application thereof

By introducing a composite nucleating agent of carbon nanotubes and oligomers into the polyaryl ethersulfone ketone resin, the problems of poor high-temperature mechanical properties and difficult processing of polyaryl ethersulfone resin are solved, and the polyaryl ethersulfone ketone resin is realized. Melt recrystallization and high temperature mechanical properties are improved.

CN119192681APending Publication Date: 2024-12-27JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411554163.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The polyarylethersulfone resin has a significant attenuation of mechanical properties due to the lack of protection of crystallization areas at high temperatures. The polyarylether ketone resin has difficulty in processing and forming and low glass transition temperature, making it difficult to achieve excellent high-temperature mechanical properties and heat resistance. grade.

Method used

Using a composite nucleation agent, including polyarylethersulfone ketone oligomers and carbon nanotubes dispersed thereon, reduces the nucleation barrier and provides nucleation sites through π-π interaction, and promotes crystal nucleation and growth. , improve the motility of the molecular chain of the resin matrix and realize the melt recrystallization of the polyarylethersulfone ketone resin.

Benefits of technology

By adding a micro-added nucleating agent, the crystallization behavior of the polyarylethersulfone ketone resin is significantly improved, its high-temperature mechanical properties and processing properties are improved, melt recrystallization is achieved, and glass transition temperature and heat resistance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192681A_ABST
    Figure CN119192681A_ABST
Patent Text Reader

Abstract

The invention provides a compound nucleating agent as well as a preparation method and application thereof, and belongs to the field of special engineering plastics. According to the compound nucleating agent provided by the invention, the carbon nanotubes and the polyarylethersulfone ketone oligomer can synergistically promote nucleation and growth of crystals; on one hand, biphenyl elements in molecular chains of the carbon nanotubes and the polyarylethersulfone ketone oligomer have pi-pi interaction, so that nucleation barriers can be reduced, and a large number of nucleation sites can be provided; on the other hand, the polyarylethersulfone ketone oligomer and a polyarylethersulfone ketone resin matrix have good compatibility, the movement ability of a molecular chain of the resin matrix is improved through a plasticizing effect, rearrangement and accumulation of the molecular chain are promoted, and growth of crystals is accelerated. In conclusion, only a trace amount of the compound nucleating agent provided by the invention needs to be added, so that the melting recrystallization process of the polyarylethersulfone ketone resin can be realized, and the crystallization behavior of the polyarylethersulfone ketone resin is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of special engineering plastics, and in particular to a composite nucleating agent and a preparation method and application thereof. Background Art

[0002] Polyarylethersulfone materials are a type of amorphous high-temperature-resistant thermoplastic special engineering plastics with high heat resistance, which are widely used in the fields of automobiles, electronics, aerospace, etc. However, due to the lack of protection of the crystalline area, the mechanical properties of polyarylethersulfone resins will be significantly attenuated at high temperatures.

[0003] Compared with polyarylethersulfone, semi-crystalline polyaryletherketone resin has advantages such as higher high-temperature mechanical properties and better solvent resistance, but its melting temperature is higher and processing and molding are more difficult. In addition, the glass transition temperature of polyaryletherketone is relatively low, about 144°C.

[0004] Combining the advantages of polyarylethersulfone and polyaryletherketone resins, polyarylethersulfoneketone resins can be obtained by introducing ketone groups into polyarylethersulfone resins. Compared with polyaryletherketone, this type of resin not only improves the glass transition temperature and heat resistance level, but also improves the processing performance. However, the configuration of the sulfone group in its main chain is an irregular tetrahedral structure, and the bond angles of Ar-SO2-Ar (105°) and Ar-O-Ar (124°) in the molecular chain are quite different, which destroys the regularity of the molecular chain, resulting in polyarylethersulfoneketone materials usually remaining in an amorphous state. Although the introduction of rigid biphenyl elements can improve the regularity of the polymer molecular chain, it also reduces the mobility of the molecular chain, making crystallization more difficult. Summary of the invention

[0005] The invention provides a composite nucleating agent and a preparation method and application thereof. The composite nucleating agent can accelerate the crystallization of polyarylethersulfoneketone resin.

[0006] The present invention provides a composite nucleating agent, characterized in that it comprises a polyarylethersulfoneketone oligomer and carbon nanotubes dispersed in the polyarylethersulfoneketone oligomer;

[0007] The poly(arylethersulfoneketone) oligomer has a structural formula shown in Formula I:

[0008]

[0009] The n=1-3.

[0010] Preferably, the mass ratio of the carbon nanotubes to the poly(arylethersulfoneketone) oligomer is 1:10-300.

[0011] Preferably, the carbon nanotubes have an inner diameter of 5 to 10 nm, an outer diameter of 10 to 20 nm, and a length of 5 to 30 μm.

[0012] The present invention also provides a method for preparing the composite nucleating agent described in the above technical solution, comprising the following steps:

[0013] Mixing 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone, 4,4'-difluorobenzophenone, carbon nanotubes, an alkali metal salt catalyst, a dehydrating agent and an organic solvent to carry out a polymerization reaction to obtain the composite nucleating agent;

[0014] The molar ratio of 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to 4,4'-difluorobenzophenone is 1:0.5-5;

[0015] The polymerization reaction temperature is 240-250° C. and the reaction time is 3-4 hours.

[0016] Preferably, the alkali metal salt catalyst comprises potassium carbonate and / or sodium carbonate.

[0017] Preferably, the molar ratio of the 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to the alkali metal salt catalyst is 1:1 to 1.2.

[0018] Preferably, the dehydrating agent comprises xylene.

[0019] Preferably, before the polymerization reaction, the method further comprises: subjecting the mixture obtained by the mixing to a salt-forming reaction, and then removing the dehydrating agent;

[0020] The temperature of the salt-forming reaction is 140-150° C. and the time is 1-2 hours;

[0021] The temperature for removing the dehydrating agent is 160-180° C. and the time is 2-3 hours.

[0022] Preferably, the mass ratio of the total mass of the 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone, 4,4'-difluorobenzophenone and the alkali metal salt catalyst to the organic solvent is 1:2-6.

[0023] The present invention also provides the use of the composite nucleating agent described in the above technical solution or the composite nucleating agent prepared by the preparation method described in the above technical solution in the preparation of crystalline polyarylethersulfoneketone.

[0024] The carbon nanotubes and poly(arylethersulfoneketone) oligomers in the composite nucleating agent provided by the present invention can synergistically promote the nucleation and growth of crystals: on the one hand, there is a π-π interaction between the carbon nanotubes and the biphenyl elements in the molecular chain of the poly(arylethersulfoneketone) oligomer, which can reduce its nucleation barrier and provide a large number of nucleation sites; on the other hand, the poly(arylethersulfoneketone) oligomer has good compatibility with the poly(arylethersulfoneketone) resin matrix, and improves the mobility of the resin matrix molecular chain through the plasticizing effect, promotes the rearrangement and stacking of the molecular chain, and accelerates the growth of crystals. In summary, the composite nucleating agent provided by the present invention only needs to be added in a trace amount to realize the melt recrystallization process of the poly(arylethersulfoneketone) resin and improve its crystallization behavior. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the infrared spectra of the composite nucleating agent of Examples 1 to 4;

[0026] Figure 2 The DSC temperature rise curve of the composite nucleating agent of Examples 1 to 4;

[0027] Figure 3 The DSC temperature drop curve of the composite nucleating agent of Examples 1 to 4;

[0028] Figure 4 This is the DSC graph of the poly(arylethersulfoneketone) composition of Application Example 1. DETAILED DESCRIPTION

[0029] The present invention provides a composite nucleating agent, comprising a polyarylethersulfoneketone oligomer and carbon nanotubes dispersed in the polyarylethersulfoneketone oligomer;

[0030] The poly(arylethersulfoneketone) oligomer has a structural formula shown in Formula I:

[0031]

[0032] The n=1-3.

[0033] In the present invention, the mass ratio of the carbon nanotubes to the poly(arylethersulfoneketone) oligomers is preferably 1:10-300. In a specific embodiment of the present invention, the mass ratio of the carbon nanotubes to the poly(arylethersulfoneketone) oligomers may be 1:10, 1:30, 1:50, 1:60, 1:100, 1:150, 1:200, 1:250 or 1:300.

[0034] In the present invention, the carbon nanotubes preferably include multi-walled carbon nanotubes; the inner diameter of the carbon nanotubes is preferably 5 to 10 nm, the outer diameter is preferably 10 to 20 nm, and the length is preferably 5 to 30 μm.

[0035] The present invention also provides a method for preparing the composite nucleating agent described in the above technical solution, comprising the following steps:

[0036] Mixing 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone, 4,4'-difluorobenzophenone, carbon nanotubes, an alkali metal salt catalyst, a dehydrating agent and an organic solvent to carry out a polymerization reaction to obtain the composite nucleating agent;

[0037] The molar ratio of 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to 4,4'-difluorobenzophenone is 1:0.5-5;

[0038] The polymerization reaction temperature is 240-250° C. and the reaction time is 3-4 hours.

[0039] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.

[0040] In the present invention, the molar ratio of 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to 4,4'-difluorobenzophenone is 1:0.5-5; in a specific embodiment of the present invention, the molar ratio of 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to 4,4'-difluorobenzophenone can be 1:0.5, 1:1, 1:1.5, 1:2, 1:3, 1:4 or 1:5.

[0041] In the present invention, the molar ratio of the 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to the alkali metal salt catalyst is preferably 1:1-1.2; the alkali metal salt catalyst preferably includes potassium carbonate and / or sodium carbonate.

[0042] In the present invention, the solid-liquid ratio of the 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to the dehydrating agent is preferably 1g:0.5-3.5mL. In a specific embodiment of the present invention, the solid-liquid ratio of the 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to the dehydrating agent may be 1g:0.5mL, 1g:1mL, 1g:1.5mL, 1g:2mL, 1g:2.5mL, 1g:3mL or 1g:3.5mL; the dehydrating agent preferably comprises xylene.

[0043] In the present invention, the mass ratio of the total mass of the 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone, 4,4'-difluorobenzophenone and the alkali metal salt catalyst to the organic solvent is preferably 1:2-6. In a specific embodiment of the present invention, the mass ratio of the total mass of the 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone, 4,4'-difluorobenzophenone and the catalyst to the organic solvent may be 1:2, 1:3, 1:4, 1:5 or 1:6; the organic solvent preferably includes diphenyl sulfone.

[0044] In the present invention, before the polymerization reaction, the mixture obtained by mixing is preferably subjected to a salt-forming reaction, and then the dehydrating agent is removed.

[0045] In the present invention, the temperature of the salt-forming reaction is preferably 140-150°C. In a specific embodiment of the present invention, the temperature of the salt-forming reaction may be 140°C, 145°C or 150°C. The time is preferably 1-3h. In a specific embodiment of the present invention, the time of the salt-forming reaction may be 1h, 2h or 3h. The salt-forming reaction is preferably carried out in an inert environment.

[0046] In the salt-forming reaction, 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone reacts with an alkali metal salt catalyst to generate salt and water, and the water generated by the salt-forming reaction is also removed in the salt-forming reaction.

[0047] In the present invention, the temperature for removing the dehydrating agent is preferably 160-180°C. In a specific embodiment of the present invention, the temperature for removing the dehydrating agent may be 160°C, 170°C or 180°C. The time is preferably 2-3h. In a specific embodiment of the present invention, the time for removing the dehydrating agent may be 2h, 2.5h or 3h. The removal of the dehydrating agent is preferably carried out in an inert environment.

[0048] In the present invention, the polymerization reaction temperature is 240-250°C, and in a specific embodiment of the present invention, the polymerization reaction temperature can be 240°C, 245°C or 250°C; the polymerization reaction time is 3-4h, and in a specific embodiment of the present invention, the polymerization reaction time can be 3h, 3.5h or 4h. The polymerization reaction is preferably carried out in an inert environment.

[0049] The present invention adopts an in-situ polymerization method to introduce carbon nanotubes during the preparation process so that the carbon nanotubes can be evenly dispersed in the oligomer.

[0050] After the polymerization reaction is completed, the present invention preferably mixes the obtained product with deionized water to precipitate the composite nucleating agent, and after solid-liquid separation, the obtained wet composite nucleating agent is successively crushed, washed and dried to obtain the composite nucleating agent.

[0051] The present invention also provides the use of the composite nucleating agent described in the above technical solution or the composite nucleating agent prepared by the preparation method described in the above technical solution in the preparation of a crystalline polyarylethersulfoneketone composition.

[0052] In the present invention, the preparation method of the crystalline poly(arylethersulfoneketone) composition preferably comprises:

[0053] The composite nucleating agent is mixed with the poly(arylethersulfoneketone), and then melt-blended, granulated, dried and annealed to obtain the crystalline poly(arylethersulfoneketone) composition.

[0054] Before the mixing, the present invention preferably dries the composite nucleating agent and the polyarylethersulfoneketone; the drying temperature is preferably 50-80°C, and in a specific embodiment of the present invention, the drying temperature may be 50°C, 60°C, 70°C or 80°C; the drying time is preferably 12-24h, and in a specific embodiment of the present invention, the drying time may be 12h, 15h, 18h, 20h or 24h.

[0055] In the present invention, the mixing is preferably performed in a high-speed stirrer.

[0056] In the present invention, the mass ratio of the polyaryl ether sulfone ketone to the composite nucleating agent is preferably 94.5-98.99:1.01-5.5. In a specific embodiment of the present invention, the mass ratio of the polyaryl ether sulfone ketone to the composite nucleating agent can be 98.99:1.01, 96.99:3.01, 96.95:3.05 or 96.9:3.1.

[0057] In the present invention, the melt blending is preferably carried out in a screw extruder, and the speed of the screw in the screw extruder is preferably 40 r·min -1 .

[0058] In the present invention, the temperature of the melt blending is preferably 380°C.

[0059] In the present invention, the drying temperature after granulation is preferably 100° C., and the drying time is preferably 12 h; and the drying is preferably performed under vacuum conditions.

[0060] In the present invention, the annealing temperature is preferably 300°C and the time is preferably 12 hours. The annealing is used to promote the formation of a crystalline region. The composite nucleating agent provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0061] The carbon nanotubes in the embodiment have an inner diameter of 5 to 10 nm, an outer diameter of 10 to 20 nm, and a length of 5 to 30 μm.

[0062] Example 1

[0063] Carbon nanotube / poly(arylethersulfoneketone oligomer) (0.01:1) composite nucleating agent

[0064] Carbon nanotubes (0.34 g) and xylene (60 mL) were placed in a 250 mL beaker and ultrasonicated for 2 h. Then, the mixture of carbon nanotubes and xylene, 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone (20.1235 g, 0.05 mol), 4,4'-difluorobenzophenone (16.3650 g, 0.075 mol), anhydrous sodium carbonate (5.7235 g, 0.054 mol), anhydrous potassium carbonate (0.8293 g, 0.006 mol) and diphenyl sulfone (109.5g) were placed in a three-necked flask, mechanically stirred for 0.5h under argon atmosphere, heated to 150℃, refluxed with azeotropic dehydration, refluxed with water for 2h, heated to 180℃ and kept for 2h to remove the azeotropic dehydrating agent xylene, heated to 240℃, continued to react for 3h, precipitated the obtained polymer solution in deionized water, separated, crushed, washed and dried to obtain a carbon nanotube / poly(arylethersulfoneketone) oligomer (0.01:1) composite nucleating agent. Wherein, n in the poly(arylethersulfoneketone) oligomer is 1 to 3.

[0065] Example 2

[0066] Carbon nanotube / poly(arylethersulfoneketone oligomer) (0.01:3) composite nucleating agent

[0067] Carbon nanotubes (0.11 g) and xylene (60 mL) were placed in a 250 mL beaker and ultrasonicated for 2 h. Then, the mixture of carbon nanotubes and xylene, 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone (20.1235 g, 0.05 mol), 4,4'-difluorobenzophenone (16.3650 g, 0.075 mol), anhydrous sodium carbonate (5.7235 g, 0.054 mol), anhydrous potassium carbonate (0.8293 g, 0.006 mol) and diphenyl sulfone (109.5g) were placed in a three-necked flask, mechanically stirred for 0.5h under argon atmosphere, heated to 150℃, refluxed with azeotropic dehydration, refluxed with water for 2h, heated to 180℃ and kept for 2h to remove the azeotropic dehydrating agent xylene, heated to 240℃, continued to react for 3h, precipitated the obtained polymer solution in deionized water, separated, crushed, washed and dried to obtain a carbon nanotube / poly(arylethersulfoneketone) oligomer (0.01:3) composite nucleating agent. Wherein, n in the poly(arylethersulfoneketone) oligomer is 1 to 3.

[0068] Example 3

[0069] Carbon nanotube / poly(arylethersulfoneketone) oligomer (0.05:3) composite nucleating agent

[0070] Carbon nanotubes (0.57 g) and xylene (60 mL) were placed in a 250 mL beaker and ultrasonicated for 2 h. Then, the mixture of carbon nanotubes and xylene, 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone (20.1235 g, 0.05 mol), 4,4'-difluorobenzophenone (16.3650 g, 0.075 mol), anhydrous sodium carbonate (5.7235 g, 0.054 mol), anhydrous potassium carbonate (0.8293 g, 0.006 mol) and diphenyl sulfone (109.5g) were placed in a three-necked flask, mechanically stirred for 0.5h under argon atmosphere, heated to 150℃, refluxed with azeotropic dehydration, refluxed with water for 2h, heated to 180℃ and kept for 2h to remove the azeotropic dehydrating agent xylene, heated to 240℃, continued to react for 3h, precipitated the obtained polymer solution in deionized water, separated, crushed, washed and dried to obtain a carbon nanotube / poly(arylethersulfoneketone) oligomer (0.05:3) composite nucleating agent. Wherein, n in the poly(arylethersulfoneketone) oligomer is 1 to 3.

[0071] Example 4

[0072] Carbon nanotube / poly(arylethersulfoneketone oligomer) (0.1:3) composite nucleating agent

[0073] Carbon nanotubes (1.15 g) and xylene (65 mL) were placed in a 250 mL beaker and ultrasonicated for 2 h. Then, the mixture of carbon nanotubes and xylene, 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone (20.1235 g, 0.05 mol), 4,4'-difluorobenzophenone (16.3650 g, 0.075 mol), anhydrous sodium carbonate (5.7235 g, 0.054 mol), anhydrous potassium carbonate (0.8293 g, 0.006 mol) and diphenyl sulfone (109.5g) were placed in a three-necked flask, mechanically stirred for 0.5h under argon atmosphere, heated to 150℃, refluxed with azeotropic dehydration, refluxed with water for 2h, heated to 180℃ and kept for 2h to remove the azeotropic dehydrating agent xylene, heated to 240℃, continued to react for 3h, precipitated the obtained polymer solution in deionized water, separated, crushed, washed and dried to obtain a carbon nanotube / polyarylethersulfoneketone oligomer (0.1:3) composite nucleating agent. Wherein, n in the polyarylethersulfoneketone oligomer is 1 to 3.

[0074] The products of Examples 1 to 4 were characterized by infrared spectroscopy. Figure 1 .

[0075] Depend on Figure 1 It can be seen that the infrared spectrum shows the characteristic peaks of the polymer, proving the successful preparation of the target product.

[0076] The products of Examples 1 to 4 were characterized by DSC, and the temperature rise curves were shown in FIG. Figure 2 The cooling curve is shown in Figure 3 .

[0077] Depend on Figures 2-3 It can be seen that the nucleating agent prepared by the present invention has good crystallization performance.

[0078] Application Example 1

[0079] The nucleating agent and poly(aryl ether sulfone ketone) prepared in Example 1 (logarithmic viscosity η = 0.68) were dried in a vacuum oven at 100°C for 12 hours. The nucleating agent and poly(aryl ether sulfone ketone) powder were added into a high-speed mixer in a mass ratio of 1.01:98.99 and mixed thoroughly. Then, the mixture was added into a twin-screw extruder and the temperature was 380°C and the screw speed was 40 r·min. -1 The obtained pellets were placed in a vacuum oven and dried at 100° C. for 12 h, and then annealed at 300° C. for 12 h to obtain a polyarylethersulfoneketone composition 1.

[0080] Application Example 2

[0081] The nucleating agent and poly(aryl ether sulfone ketone) prepared in Example 2 (logarithmic viscosity η = 0.68) were dried in a vacuum oven at 100°C for 12 hours. The nucleating agent and poly(aryl ether sulfone ketone) powder were added into a high-speed mixer in a mass ratio of 3.01:96.99 and mixed thoroughly. Then, the mixture was added into a twin-screw extruder and the temperature was 380°C and the screw speed was 40 r·min. -1 The obtained pellets were placed in a vacuum oven and dried at 100° C. for 12 h, and then annealed at 300° C. for 12 h to obtain a polyarylethersulfoneketone composition 2.

[0082] Application Example 3

[0083] The nucleating agent and poly(aryl ether sulfone ketone) prepared in Example 3 (logarithmic viscosity η = 0.68) were dried in a vacuum oven at 100°C for 12 hours. The nucleating agent and poly(aryl ether sulfone ketone) powder were added into a high-speed mixer in a mass ratio of 3.05:96.95 and mixed thoroughly. Then, the mixture was added into a twin-screw extruder and the temperature was 380°C and the screw speed was 40 r·min. -1 The obtained pellets were placed in a vacuum oven and dried at 100° C. for 12 h, and then annealed at 300° C. for 12 h to obtain a polyarylethersulfoneketone composition 3.

[0084] Application Example 4

[0085] The nucleating agent and poly(aryl ether sulfone ketone) prepared in Example 4 (logarithmic viscosity η = 0.68) were dried in a vacuum oven at 100°C for 12 hours. The nucleating agent and poly(aryl ether sulfone ketone) powder were added into a high-speed mixer in a mass ratio of 3.1:96.9 and mixed thoroughly. Then, the mixture was added into a twin-screw extruder and the temperature was 380°C and the screw speed was 40 r·min. -1 The obtained pellets were placed in a vacuum oven and dried at 100° C. for 12 h, and then annealed at 300° C. for 12 h to obtain a polyarylethersulfoneketone composition 4.

[0086] Comparative application example 1

[0087] The poly(aryl ether sulfone ketone) (logarithmic viscosity η = 0.68) was dried in a vacuum oven at 100 °C for 12 h. Without adding a nucleating agent, the poly(aryl ether sulfone ketone) powder was added to a twin-screw extruder at a temperature of 380 °C and a screw speed of 40 r / min. -1 The obtained pellets were placed in a vacuum oven and dried at 100° C. for 12 h and then annealed at 300° C. for 12 h to obtain polyarylethersulfoneketone.

[0088] The poly(aryl ether sulfone ketone) compositions of Examples 1 to 4 and the poly(aryl ether sulfone ketone) of Comparative Example 1 were subjected to DSC characterization. The results are shown in FIG. Figure 4 .

[0089] Depend on Figure 4 It can be seen that the prepared nucleating agent has a good nucleating effect, improves the crystallization behavior of poly(arylethersulfoneketone) resin, and successfully realizes its melt recrystallization.

[0090] Table 1 Melting enthalpy values ​​after annealing in Application Examples 1 to 4 and Comparative Application Example 1

[0091]

[0092] According to the test results in Table 1, the carbon nanotube / poly(arylethersulfoneketone) oligomer composite nucleating agent provided by the present invention can successfully achieve recrystallization of poly(arylethersulfoneketone) after melting, and the melting enthalpy value is 9.5-14.5 J / g.

[0093] In summary, the present invention controls the carbon nanotube content in the polyarylethersulfoneketone resin matrix between 0.01% and 0.1%, controls the oligomer content between 1% and 3%, and uniformly disperses the carbon nanotubes on the polyarylethersulfoneketone oligomer, thereby improving the crystallization behavior of the polyarylethersulfoneketone resin and successfully achieving its melt recrystallization.

[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite nucleating agent, characterized in that: It comprises a polyarylethersulfoneketone oligomer and carbon nanotubes dispersed in the polyarylethersulfoneketone oligomer; The poly(arylethersulfoneketone) oligomer has a structural formula shown in Formula I: The n=1-3.

2. The composite nucleating agent according to claim 1, characterized in that: The mass ratio of the carbon nanotube to the polyarylethersulfoneketone oligomer is 1:10-300.

3. The composite nucleating agent according to claim 1, characterized in that: The carbon nanotube has an inner diameter of 5 to 10 nm, an outer diameter of 10 to 20 nm, and a length of 5 to 30 μm.

4. The method for preparing the composite nucleating agent according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mixing 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone, 4,4'-difluorobenzophenone, carbon nanotubes, an alkali metal salt catalyst, a dehydrating agent and an organic solvent to carry out a polymerization reaction to obtain the composite nucleating agent; The molar ratio of 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to 4,4'-difluorobenzophenone is 1:0.5-5; The polymerization reaction temperature is 240-250° C. and the reaction time is 3-4 hours.

5. The preparation method according to claim 4, characterized in that: The alkali metal salt catalyst includes potassium carbonate and / or sodium carbonate.

6. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of the 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone to the alkali metal salt catalyst is 1:1 to 1.

2.

7. The preparation method according to claim 4, characterized in that: The dehydrating agent includes xylene.

8. The preparation method according to claim 4 or 7, characterized in that: Before the polymerization reaction, the method further comprises: subjecting the mixture obtained by the mixing to a salt-forming reaction, and then removing the dehydrating agent; The temperature of the salt-forming reaction is 140-150° C. and the time is 1-2 hours; The temperature for removing the dehydrating agent is 160-180° C. and the time is 2-3 hours.

9. The preparation method according to claim 4, characterized in that: The mass ratio of the total mass of the 4,4'-bis(4-hydroxyphenyl)diphenyl sulfone, 4,4'-difluorobenzophenone and the alkali metal salt catalyst to the organic solvent is 1:2-6.

10. Use of the composite nucleating agent according to any one of claims 1 to 3 or the composite nucleating agent prepared by the preparation method according to any one of claims 4 to 9 in preparing a crystalline polyarylethersulfoneketone composition.